Financial hardship screening among Native American patients with cancer: a qualitative analysis - Amber S. Anderson-Buettner; Amanda E. Janitz; Mark P. Doescher; Stefanie D. Madison; Michaela A. Khoussine; Keri L. Harjo; Marvin B. Bear; Stephnie Dartez; Sheryl K. Buckner; Dorothy A. Rhoades (BMC, 2024)
Abstract Background Cancer-related financial hardship is an increasingly recognized concern for patients, families, and caregivers. Many Native American (NA) patients are at increased risk for cancer-related financial hardship due to high prevalence of low income, medical comorbidity, and lack of private health insurance. However, financial hardship screening (FHS) implementation for NA patients with cancer has not been reported. The objective of this study is to explore facilitators and barriers to FHS implementation for NA patients. Methods We conducted key informant interviews with NA patients with cancer and with clinical staff at an academic cancer center. Included patients had a confirmed diagnosis of cancer and were referred to the cancer center through the Indian Health Service, Tribal health program, or Urban Indian health program. Interviews included questions regarding current financial hardship, experiences in discussing financial hardship with the cancer care and primary care teams, and acceptability of completing a financial hardship screening tool at the cancer center. Clinical staff included physicians, advanced practice providers, and social workers. Interviews focused on confidence, comfort, and experience in discussing financial hardship with patients. Recorded interviews were transcribed and thematically analyzed using MAXQDA® software. Results We interviewed seven patients and four clinical staff. Themes from the interviews included: 1) existing resources and support services; 2) challenges, gaps in services, and barriers to care; 3) nuances of NA cancer care; and 4) opportunities for improved care and resources. Patients identified financial challenges to receiving cancer care including transportation, lodging, food insecurity, and utility expenses. Patients were willing to complete a FHS tool, but indicated this tool should be short and not intrusive of the patient's financial information. Clinical staff described discomfort in discussing financial hardship with patients, primarily due to a lack of training and knowledge about resources to support patients. Having designated staff familiar with I/T/U systems was helpful, but perspectives differed regarding who should administer FHS. Conclusions We identified facilitators and barriers to implementing FHS for NA patients with cancer at both the patient and clinician levels. Findings suggest clear organizational structures and processes are needed for financial hardship to be addressed effectively.